This preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: WC(Ti – T o )  WC(T 1 – T o ) = ρ C V dt dT 1 (1) At steady state WC(Tis – T o )  WC(T 1 s – T o ) = 0 (2) (1) – (2) gives WC(Ti – Tis)  WC(T 1 – T 1s ) = ρ C V dt dT 1 ' WTi ’ WT 1 ’ = ρ V dt dT 1 ' Taking Laplace transform WTi(s) = WT 1 (s) + ρ V s T 1 (s) s s Ti s T τ + = 1 1 ) ( ) ( 1 , where τ = ρ V / W. From tank 2 q + WC(T 1 – T o )  WC(T 2 – T o ) = ρ C V dt dT 2 (3) At steady state q s + WC(T 1s – T o )  WC(T 2s – T o ) = 0 (4) (3) – (4) gives Q ‘ + WC(T 1 – T 1s )  WC(T 2 – T 2s ) = ρ C V dt dT 2 ' Q ‘ + WCT 1 ’ WCT 2 ’ = ρ C V dt dT 2 ' Taking Laplace transform...
View
Full Document
 Spring '10
 Koslov
 Thermodynamics, Laplace, dt

Click to edit the document details